2011
DOI: 10.1002/rcm.5184
|View full text |Cite
|
Sign up to set email alerts
|

A tandem mass spectrometric investigation of N‐(3‐ferrocenyl‐2‐naphthoyl) dipeptide ethyl esters and N‐(6‐ferrocenyl‐2‐naphthoyl) dipeptide ethyl esters

Abstract: N-(3-Ferrocenyl-2-naphthoyl) dipeptide ethyl esters 1-4 and N-(6-ferrocenyl-2-naphthoyl) dipeptide ethyl esters 5-8 were prepared by coupling either 3-ferrocenylnaphthalene-2-carboxylic acid or 6-ferrocenylnaphthalene-2-carboxylic acid to the dipeptide ethyl esters GlyGly(OEt) (1, 5), AlaGly(OEt) (2, 6), GlyPhe(OEt) (3, 7) and GlyLeu(OEt) (4, 8), using the standard N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, 1-hydroxybenzotriazole protocol. Electrospray ionization mass spectrometry (ESI-MS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In the recent years, considerable experimental and theoretical calculation studies have demonstrated that ferrocene and some of its derivatives are easily oxidized during electrospray ionization (ESI) with the formation of molecular ions . However, the details of the fragmentation mechanisms of protonated benzoylferrocenes in collision‐induced dissociation (CID) mass spectrometry (MS) have not been obtained.…”
mentioning
confidence: 99%
“…In the recent years, considerable experimental and theoretical calculation studies have demonstrated that ferrocene and some of its derivatives are easily oxidized during electrospray ionization (ESI) with the formation of molecular ions . However, the details of the fragmentation mechanisms of protonated benzoylferrocenes in collision‐induced dissociation (CID) mass spectrometry (MS) have not been obtained.…”
mentioning
confidence: 99%